2010
DOI: 10.1016/j.fsi.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Searching for immunomodulatory sequences in sea bass (Dicentrarchus labrax L.): Transcripts analysis from thymus

Abstract: The thymus is a key organ of the immune system in most vertebrates and, for this reason, it has been used in this paper for the generation of a normalized cDNA library from sea bass (Dicentrarchus labrax), one of the most extensively cultured species in South Mediterranean aquaculture. A total of 1632 ESTs from this library were initially analysed for sequence quality and vector sequences and, after this control, 1264 (77% of total clones sequenced) high-quality ESTs were further processed. The total collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 56 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Two different Mx genes had been identified in European sea bass, proving that the isoform MxA is particularly modulated in nodavirus-infected sea bass [20, 46]. As previously shown [47], the ISG12 gene can also be employed in sea bass as a marker of antiviral activities, since this ISG isoform is well expressed in gills [22], and significant ISG12 gene modulation can be induced in sea bass after in vitro stimulation with virus-mimicking substance poly I:C [47]. …”
Section: Discussionmentioning
confidence: 82%
“…Two different Mx genes had been identified in European sea bass, proving that the isoform MxA is particularly modulated in nodavirus-infected sea bass [20, 46]. As previously shown [47], the ISG12 gene can also be employed in sea bass as a marker of antiviral activities, since this ISG isoform is well expressed in gills [22], and significant ISG12 gene modulation can be induced in sea bass after in vitro stimulation with virus-mimicking substance poly I:C [47]. …”
Section: Discussionmentioning
confidence: 82%
“…As mentioned above, in mammals, DN cells undergo V(D)J rearrangement to express TCR α and β-chains. Several studies reported the expression of Rag-1 and Rag-2 located in the thymus of zebrafish, rainbow trout, red-spotted grouper (Epinephelus akaara), medaka, goldfish (Carassius auratus), fugu, carp, Atlantic salmon and Atlantic halibut [74][75][76][77][78][79][80][81][82][83]. The rag gene expression suggested a conserved mechanism for TCRβchain rearrangement which is a crucial step for pre-TCR expression.…”
Section: Functionmentioning
confidence: 99%
“…CD83 sequence was identified after Expressed Sequence Tag (EST) sequencing of a sea bass thymus cDNA library as described previously [17]. The library was normalized to facilitate the identification and analysis of rare transcripts.…”
Section: Sea Bass Cd83 Sequence Identification and Analysismentioning
confidence: 99%